Lithium induces corticotropin secretion and desensitization in cultured anterior pituitary cells. - Zatz, M (1985)
Lithium stimulated corticotropin (ACTH) secretion by mouse pituitary tumor cells (AtT-20/D16-16) and by normal rat anterior pituitary cells in primary culture. Effects were observed at less than 2 mM LiCl. ACTH secretion was comparable in magnitude to that induced by other secretagogues, was calcium dependent, and was inhibited by somatostatin. Lithium also induced changes in [3H]inositide metabolism; these changes accompanied and were correlated with changes in ACTH secretion. The most prominent and reliable effect was to increase [3H]inositol monophosphate. Other secretagogues had no effect on [3H]inositides in the presence or absence of lithium. Pretreatment with lithium for 3 hr desensitized the cells to the effects of subsequent exposure to lithium. The cells were not desensitized to lithium by pretreatment with other secretagogues, nor were they desensitized by lithium to the effects of corticotropin-releasing factor, high potassium, or forskolin. However, pretreatment with lithium did desensitize the cells to stimulation by phorbol esters. The interaction between lithium and phorbol esters suggests the involvement of inositide metabolism and protein kinase C in the regulation of ACTH secretion and possibly of other hormones or neurotransmitters. It also suggests new avenues of research into the basis of lithium's psychopharmacological effects.